(untitled) (Prosiding SEMDIKJAR (Seminar Nasional Pendidikan dan Pembelajaran), 2025)
Erlangga interactive multimedia based on Problem Based Learning was declared valid based on the validation results of media experts who obtained a score of 82% and included in the very valid criteria. Validation of material experts showed a score of 85%, also in the very valid category. The average assessment of media experts and material experts reached 84%, which means this multimedia is very valid to use. In addition, Erlangga multimedia was declared practical. The teacher response questionnaire obtained a score of 87% which indicates the criteria are very practical to use in learning. Student responses obtained a score of 79%, which is included in the practical category. The average score of teacher and student responses was 83%, so this multimedia is classified as very practical. In terms of effectiveness, there was a significant difference between the post-test results of the experimental class and the control class, with a p value <0.05 (2-tailed) that is p = 0.000. The average post-test score of the experimental class was higher than the control class. This shows that Erlangga interactive multimedia based on Problem Based Learning is effective in improving student learning outcomes on the material of changes in the state of matter.